Pola Kepemimpinan Yesus dalam Injil Yohanes Teladan Pemimpin Kristen Masa Kini - Reni Herayani Manik; Sofia Sri Soradinah Wau; Ibelala Gea (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Writing this article is based on the fact that there are still many Christian leaders today who abuse their leadership without seeing the context of their faith in God's love. Therefore the purpose of writing this scientific work is how readers can emulate Jesus' leadership in the Gospel of John, the method used in writing this article is qualitative analysis through literature study by analyzing how Jesus' leadership example is very relevant for today's Christian leadership, which can be taken through books, articles. Bible and journal. The conclusion from the results of this study is that the leadership that Jesus did cannot be denied and doubted for today's Christian leaders, because he proved that he had shown how to be a quality leader even though Jesus himself could master what he wanted but not with Jesus who always humble.